Penerapan Prinsip Hukum Ekonomi Syariah dalam Penyelesaian Wanprestasi Akad Murabahah: Studi Kasus di Pengadilan Agama Situbondo - Fadlila, Annisa Zakiyatul; Muallifin, Darin Arif (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
Murabahah financing, as a prevalent Islamic banking product, frequently encounters default issues requiring resolution that aligns with sharia principles. This study aims to analyze the application of sharia economic law principles in resolving Murabahah contract defaults at the Situbondo Religious Court. Employing a qualitative method with a normative juridical approach, this research analyzes court verdict documents as primary data, supplemented by DSN-MUI fatwas and relevant literature as secondary data. The findings indicate that while the Murabahah contract formally fulfilled its pillars and conditions, the implementation of sharia principles in default resolution faced challenges, particularly regarding the imposition of late penalties that did not fully reflect the principles of justice (al-'adl) and compensatory damages (ta'widh). The study concludes that despite procedural adherence, substantive sharia compliance requires greater attention, especially in sanction clauses. It recommends enhanced socialization and assistance for sharia financial institutions to ensure comprehensive alignment of financing practices with sharia principles, encompassing both formal and substantive aspects of the contract.